MAKNA DAN NILAI TUTURAN DALAM TRADISI ORE ANA DI DESA PUHU KECAMATAN ADONARA TIMUR KABUPATEN FLORES TIMUR - Maria Faustina Kewa Saya; Hiwa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study discusses the meaning and values contained in the Ore Ana tradition of Puhu Village, East Adonara District, East Flores Regency. The Ore Ana tradition is a cultural heritage of the Lamaholot community, reflecting deep philosophical, religious, and spiritual meanings. The purpose of this research is to describe the meanings expressed in the ritual speeches and to explore the cultural and moral values they embody. The study employs a literature review method by analyzing relevant scholarly sources and previous studies on Lamaholot culture and the Ore Ana tradition. The findings reveal that the speeches in Ore Ana contain religious, spiritual, and petition meanings, as well as cultural and religious values that reflect the close relationship between humans, ancestors, and God. The Ore Ana tradition serves as a medium for preserving cultural identity and transmitting moral education for the younger generation of Lamaholot society.